2024
DOI: 10.3390/plants13050672
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promotion and Plant Disease Suppression Induced by Bacillus amyloliquefaciens Strain GD4a

Piao Yang,
Pu Yuan,
Wenshan Liu
et al.

Abstract: Botrytis cinerea, the causative agent of gray mold disease (GMD), invades plants to obtain nutrients and disseminates through airborne conidia in nature. Bacillus amyloliquefaciens strain GD4a, a beneficial bacterium isolated from switchgrass, shows great potential in managing GMD in plants. However, the precise mechanism by which GD4a confers benefits to plants remains elusive. In this study, an A. thaliana-B. cinerea-B. amyloliquefaciens multiple-scale interaction model was used to explore how beneficial bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
0
0
0
Order By: Relevance
“…Over the years, biocontrol has emerged as an effective, safe, and environmentally friendly method for plant disease management, reducing the reliance on synthetic agrochemicals [ 29 , 30 ]. B. amyloliquefaciens , a species within the Bacillus genus, has shown potential as a biocontrol agent against plant pathogens [ 31 , 32 , 33 ]. Previous studies have reported that B. amyloliquefaciens can effectively control rice blast [ 18 , 34 ], but the mechanisms underlying its inhibition of M. oryzae remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, biocontrol has emerged as an effective, safe, and environmentally friendly method for plant disease management, reducing the reliance on synthetic agrochemicals [ 29 , 30 ]. B. amyloliquefaciens , a species within the Bacillus genus, has shown potential as a biocontrol agent against plant pathogens [ 31 , 32 , 33 ]. Previous studies have reported that B. amyloliquefaciens can effectively control rice blast [ 18 , 34 ], but the mechanisms underlying its inhibition of M. oryzae remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are a pivotal mechanism in controlling plant diseases through the secretion of lipopeptide substance, polyketide compounds, and antimicrobial proteins [ 55 ]. Among these secondary metabolites, lipopeptides are extensively studied as antimicrobial agents and are categorized into three main groups based on their structure: iturins, surfactins, and fengycins [ 56 ]. Studies have demonstrated that the inhibitory effects of lipopeptides on pathogens primarily manifest in the suppression of mycelial growth and impact spore germination.…”
Section: Discussionmentioning
confidence: 99%